Ligand- and Additive-Free 2-Position-Selective Trifluoromethylation of Heteroarenes Under Ambient Conditions - Shi, Xiaolin; Li, Xiaowei; Li, Xiangqian; Shi, Dayong (Frontiers in Chemistry, 2019)
A highly selective copper-catalyzed trifluoromethylation of indoles is reported with the assistance of a removable directing group. This protocol provides an easy and rapid method to various 2-position-selective trifluoromethylated heteroarenes including indoles, pyrroles, benzofuran, and acetanilide. What is more, the reaction takes place at ambient conditions without any external ligand or additive.